2005
DOI: 10.1038/ng1635
|View full text |Cite
|
Sign up to set email alerts
|

Sipa1 is a candidate for underlying the metastasis efficiency modifier locus Mtes1

Abstract: Previously, using an inbred strain screen and QTL mapping strategies, we demonstrated the presence of loci in the mouse genome that significantly influenced the ability of a transgene-induced mammary tumor to metastasize to the lung. Here we present data supporting the signal transduction molecule, Sipa1, as a candidate for the metastasis efficiency modifier locus Mtes1. Sequence analysis of genes in a candidate haplotype block revealed a non-synonymous animo acid polymorphism in the Sipa1 PDZ protein-protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 60 publications
(2 reference statements)
6
144
1
1
Order By: Relevance
“…What is apparent is that the BRD4-SIPA1-RRP1B relationship seems to be a critical node in this ECM/tumor progression transcriptional network. SIPA1 is a potent modulator of metastatic efficiency in mice, which may relate to its RAPGAP activity [9]. Furthermore, we have demonstrated that SIPA1 is a tumor progression susceptibility gene in humans [34].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…What is apparent is that the BRD4-SIPA1-RRP1B relationship seems to be a critical node in this ECM/tumor progression transcriptional network. SIPA1 is a potent modulator of metastatic efficiency in mice, which may relate to its RAPGAP activity [9]. Furthermore, we have demonstrated that SIPA1 is a tumor progression susceptibility gene in humans [34].…”
Section: Discussionmentioning
confidence: 72%
“…These results suggested that metastasis susceptibility was likely to be due not only to somatic events occurring during the evolution of the tumor, but also due to combinations of inherited germline polymorphisms acting in concert to modulate the probability of whether a tumor will progress. Further investigation of these initial observations allowed us to identify two of these polymorphic metastasis susceptibility genes that modulate metastasis in both mouse and human: the Rap-GTPase activating protein (GAP) Sipa1 [9]; and Rrp1b, a gene that modulates the enzymatic activity of Sipa1 [10].…”
Section: Introductionmentioning
confidence: 99%
“…3. metastatic capacity of a mouse breast cancer cell line (19). Nme3 is highly expressed in solid tumor cell lines and may contribute to the differentiative arrest of myeloid leukemia cells (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Although many investigations have focused on identifying factors that affect initial tumor development (2,3), data from both human and mouse studies have demonstrated that genetic polymorphisms can modulate multiple aspects of tumorigenesis, such as tumor progression (4)(5)(6) and response to therapy (7).…”
mentioning
confidence: 99%